Macroeconomic Stress-Test and Sensitivity Analysis of Financial Industry Credit Risk: An Example from The US Market - Nugroho, Anggoro Budi (Jurnal Manajemen Teknologi, 2011)
This paper seeks to implement simple stress-test analysis using OLS method to understand banking industry sensitivity to macroeconomic risk in US financial market from 2005 to 2008.Some observations made upon a couple of variables such as exchange rates of five world currenciesto US dollar, short and long-term US Treasury Bills rates, US inflation rate, the central bank's discount rate, and other two sort of banks' interest rates being bank primeloan and home mortgage rate.These independent variables were estimated in four different constructs for their influence to delinquency risk,, the type of credit risk that banking industry is basically dealing with in common. The findings resulted in fact that Australian Dollar (AUD) is the riskiest currency to banks's credit loss during the period. Similar positive impact were aalso shown by the bank primeloan rate, and federal funds rate, meaning that US central bank's monetary policy still has significant impact to the industry's basic risk.. When exchange rates observation window was extended to further previous year, Japanese Yen was found the most volatile.Keywords: Credit Risk, Stress-Test, Macroeconomic Risks, Delinquency Rate, Sensitivity Analysis, Central Bank Discretion.